2007
DOI: 10.1530/eje-07-0355
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and metabolic responses to extreme altitude and physical exercise in climbers

Abstract: Context: Chronic hypoxia induces complex metabolic and endocrine adaptations. High-altitude (HA) exposure is a physiological model of hypoxia. Objective: To further investigate the endocrine and metabolic responses to extreme HA. Methods: We studied nine male elite climbers at sea level and at 5200 m after climbing Mt. Everest. Results: After 7 weeks at HA, body weight was reduced (P!0.05); regarding endocrine variables we observed: a) an increase of 2-h mean GH concentration (P!0.05) as well as of total IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 34 publications
7
106
3
10
Order By: Relevance
“…Hereafter, normalization of glucose concentrations occurs again, and these changes in glucose concentrations are paralleled by similar changes in epinephrine concentrations (42). Cortisol concentrations seem to follow this same pattern, while growth hormone concentrations seem to be increased only after a prolonged stay at very high or extreme altitudes (39,45).…”
Section: Acclimatizationmentioning
confidence: 87%
“…Hereafter, normalization of glucose concentrations occurs again, and these changes in glucose concentrations are paralleled by similar changes in epinephrine concentrations (42). Cortisol concentrations seem to follow this same pattern, while growth hormone concentrations seem to be increased only after a prolonged stay at very high or extreme altitudes (39,45).…”
Section: Acclimatizationmentioning
confidence: 87%
“…Published data have been somewhat inconsistent reporting an increase (12,37), a decrease (38), or no change (13,39) in leptin after ascent to HA. However, hypoxia has been shown to clearly increase leptin gene expression in adipocyte studies (40).…”
Section: Discussionmentioning
confidence: 99%
“…Former studies, investigating either HA natives or climbers exposed to HA for 2 months, have shown increased IGF1 and IGFBP3 at HA (13,26). In contrast, studies on short-term effects from exercise under hypoxic conditions revealed either no significant change or a decrease in IGF1 respectively (25,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also reported that hypoxic training could more effectively reduce arterial stiffness in postmenopausal women compared with that in normoxic training [17]. However, although body weight changes during high-altitude mountain expeditions have been described in several studies for healthy subjects [18,19], there have been very few reports on hypoxic training effects under controlled experimental conditions. The purpose of this study was to investigate the influence of hypoxic physical exercise on metabolic risk markers and to compare the effects on maximum oxygen uptake (VO 2max ), arterial stiffness, and several blood parameters related to MS to a control group training under normoxic conditions.…”
Section: Introductionmentioning
confidence: 99%